Effectiveness of interventions in patients with speech disorders. A meta-analysis of experimental studies - Camelia Daniela Cucu; Florinda Golu; Andreea Raluca Adam (Romanian Journal of Neurology, 2021)
Objectives. The study aims to conduct a meta-analysis on the existence of solid experimental evidence to highlight the effectiveness of interventions in the improvement of speech disorders in patients who have suffered a stroke. It is desired to identify those moderating variables that can influence the effectiveness of these interventions over time, or that demonstrate the extent to which chronicity of stroke may lead to inferior results in speech improvement. Materials and methods. A search was conducted in three databases: Cochrane Library, Web of Science and PubMed, to identify those studies that meet the criterion for intervention, starting with the first records and until now. The qualitative analysis of the studies was performed using Risk of Bias, and the quantitative analysis through Comprehensive Meta-Analysis. Results. As a result of selection, 31 randomized clinical studies were included in the current research, out of the 1923 existing studies. These have been the subject of investigation on aphasia and dysphagia, with a wide range of types and methods of intervention. The results show that the difference in averages between the intervention group and the post-test control group is a significant one (g = 0.528; 95% CI 0.067; 0.004; p = 0.000), while the moderation analysis did not record a statistical significance. Conclusions. Non-pharmacological interventions based on the recovery of speech disorders as a result of stroke have been shown to be effective in many of the researches in specialized literature. Their results show that, as a result of therapies, patients experience improvements in quality of life, communication and many psychiatric disorders. However, it is not clear how effective these interventions are in recovering or ameliorating speech disorders.